Development of Reaction Speed and Endurance Training Tools for Taekwondo Kick Speeds Using Pyongyo - Swandana, Atika; Sugiharto, Sugiharto; Ciptaning Wahyu, Imam Santosa (Journal of Physical Education and Sports, 2021)
The background of this research is the development of technology in coaching that was increasingly diverse and requires coaches to be able to adapt to the competition. The role of the trainer is not to be divided in concentration during training. This is important because during training the trainer's duty in addition to monitor the course of the training, the coach must also be able to analyze the results of the training. The purpose of this study was to develop a speed and endurance training tool for kick speed with sensors, LEDs, and digital accounting to be used to train kick speed and endurance in taekwondo athletes. This method of this research is Research and Development which has the following steps: Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trials, Product Revision, Usage Trials, Product Revision, Bulk Products. The results of this study are from the first taekwondo expert at stage I 93% good, stage II 95% very good. The assessment of second taekwondo experts at stage I is 75% good, stage II is 95% very good. The assessment of the first electro expert at stage I is 74% good, stage II is 95% very good. The evaluation of second electro experts in stage I is 90% very good, stage II is 95% very good. The evaluation process in trials for trainers in small group trials was 71% very good, in large group trials 89.37% was very good, in product trials 89.37% was very good.